A review of the experience of clinical attachment among undergraduate nursing students and clinical instructors - Ramli, Muhammad Afiq Ikhmal; Mahat, Nur Ain; Shaharaan, Noor Maizatul Akma; Abd Hisham, Nursyafiah Yasmin (UniKL, 2024)
Introduction: Clinical attachments benefit nursing students but present with challenges. This 2018-2023 review looks at the experience of instructors and students with clinical attachments to identify areas for development. Aims: This literature review aims to look for literature related to the experience of nursing students and clinical instructors during clinical attachment as well as how the ratio of student-to-clinical instructor affects both parties. Methods: The studies included in this study were identified through two databases: Google Scholar and ScienceDirect with keywords such as “experience”, “clinical attachment”, “clinical instructors”, “challenges”, “effect”, “inadequate”, “insufficient”, “ratio”, and “nursing students”. The published studies from 2018 onwards were included. Results: A total of 14 articles were analysed in this review after screening over 2639 articles available online. It was found that students were tasked with workload, unclear goals, and negative staff interactions. Instructors struggle to balance student needs, self-care, and workload. High student-to-teacher ratios affect both groups. Conclusion: Understanding these experiences improves clinical learning and prepares future nurses for practice.